Two new CoII coordination polymers with multifunctional 5‐amino‐2, 4, 6‐tribromoisophthalic acid and flexible isomeric bis(imidazole) ligands: preparation, crystal structure and characterization. Issue 4 (6th April 2018) - Su, Chang-Kai; Zhang, Kou-Lin
Abstract : Two new Co II coordination polymers with multifunctional 5‐amino‐2, 4, 6‐tribromoisophthalic acid (H2 ATBIP) and isomeric bis(imidazole) ligands have been prepared and characterized. Abstract : Two new Co II coordination polymers (CPs), namely, catena ‐poly[[[(5‐amino‐2, 4, 6‐tribromobenzene‐1, 3‐dicarboxylato‐κ O )aquacobalt(II)]‐bis[μ‐1, 3‐bis(imidazol‐1‐ylmethyl)benzene‐κ 2 N : N ′]] 4.75‐hydrate], {[Co(C8 H2 Br3 NO4 )(C14 H14 N4 )2 (H2 O)]·4.75H2 O} n, (1), and poly[(μ‐5‐amino‐2, 4, 6‐tribromobenzene‐1, 3‐dicarboxylato‐κ 2 O 1 : O 3 )[μ‐1, 2‐bis(imidazol‐1‐ylmethyl)benzene‐κ 2 N : N ′]cobalt(II)], [Co(C8 H2 Br3 NO4 )(C14 H14 N4 )] n, (2), have been synthesized successfully by the assembly of multifunctional 5‐amino‐2, 4, 6‐tribromoisophthalic acid (H2 ATBIP) and Co II ions in the presence of the flexible isomeric bis(imidazole) ligands 1, 3‐bis(imidazol‐1‐ylmethyl)benzene (mbix) and 1, 2‐bis(imidazol‐1‐ylmethyl)benzene (obix). The isomeric mbix and obix ligands have a big influence on the structures of CPs (1) and (2). CP (1) is composed of chains of nanometre‐sized elliptical rings, in which the Co II atom exhibits a distorted octahedral coordination geometry and ATBIP 2− acts as a monodentate ligand. Two adjacent chains are interlinked by π–π stacking interactions and hydrogen bonds, resulting in a supramolecular double chain. Hydrogen‐bonded R 8 6 (16) rings extend adjacent supramolecular double chains into a two‐dimensional supramolecular layer. Halogen bonding and a hydrogen‐bonded R 4 2 (8) ring further link the two‐dimensional supramolecular layers, leading to the formation of a three‐dimensional supramolecular network. The Co II ion in CP (2) is tetracoordinated, exhibiting a distorted tetrahedral configuration. The ATBIP 2− ligand exhibits a bis(monodentate) coordination bridging mode, linking adjacent Co II ions into zigzag chains, which are further bridged by the auxiliary bridging obix ligand, resulting in a two‐dimensional (4, 4) topological network. Interlayer hydrogen and halogen–halogen bonding further extend the two‐dimensional layers into a three‐dimensional supramolecular network. A detailed analysis of the solid‐state UV–Vis–NIR diffuse‐reflectance spectra of (1) and (2) indicates that a wide optical band gap exists in both (1) and (2). CP (1) exhibits an irreversible dehydration–rehydration behaviour.